Quantification of the left atrium applying cardiovascular magnetic resonance in clinical routine. (4th March 2018) - Funk, Stephanie; Kermer, Josephine; Doganguezel, Serkan; Schwenke, Carsten; von Knobelsdorff-Brenkenhoff, Florian; Schulz-Menger, Jeanette
Abstract: Objectives. In recent years the impact of the left atrium (LA) has become more evident in different cardiovascular pathologies. We aim to provide LA parameters in healthy volunteers for cardiovascular magnetic resonance (CMR) using a fast approach. Design. We analyzed 203 healthy volunteers (mean age 44.6 years (y), range 19y–76y) at 1.5 and 3.0 Tesla (T) using steady-state free precession (SSFP) cine in routine long axis view. Left atrial enddiastolic volume (LA-EDV), endsystolic volume (LA-ESV), stroke volume (LA-SV) and ejection fraction (LA-EF) were quantified and indexed to body-surface-area (BSA). Dependency on age and sex was analyzed. Results. 21 subjects had to be excluded. In the remaining, there was no significant difference between 1.5 T and 3.0 T. Absolut LA-EDV and LA-ESV were larger in men than in women (LA-EDV: male 70 ± 19 ml vs. female 61 ± 16 ml ( p = .001); LA-ESV: male 24 ± 9 ml vs. female 21 ± 8 ml ( p = .01)). These differences disappeared after indexing to BSA (LA-EDV/BSA: male 34 ± 10 ml/m 2 vs. female 33 ± 9 ml/m 2 ( p = .65) and LA-ESV/BSA: male 12 ± 4 ml/m 2 vs. female 11 ± 4 ml/m 2 ( p = .71)). LA-EDV/BSA decreased with older age. Conclusions. Reference values for LA size and function based on a fast approach are provided. LA size decreases with older age. Normalization to body size overcomes sex-dependency. Reports should be related to body size.